The Limits of Human Knowledge: A Critical Examination of Foundationalism and Coherentism in Epistemology - Ogar, Thomas Eneji; Aboka, George; Akiba, Esther (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
This paper critically examines the debate between foundationalism and coherentism in epistemology, assessing their ability to justify knowledge claims while addressing the inherent limits of human understanding. Foundationalism argues that knowledge rests on basic, self-evident beliefs, whereas coherentism maintains that justification emerges from the systematic interrelation of beliefs within a network. By analyzing the strengths and weaknesses of each theory, this study explores whether either can adequately respond to radical skepticism without collapsing into circularity or arbitrariness. Foundationalism’s reliance on indubitable foundations is challenged by the problem of infinite regress, while coherentism’s holistic approach risks detachment from empirical reality. The paper also considers hybrid models, such as foundherentism, as potential middle-ground solutions. Ultimately, it argues that while both theories offer valuable insights into epistemic justification, neither fully overcomes the skeptical challenge, suggesting that a pluralistic or pragmatic approach may be necessary to account for the complexities of human knowledge.